Practices of freedom : decentred governance, conflict and democratic participation - Griggs, Steven, 1962-; Norval, Aletta J.; Wagenaar, H. (Cambridge : Cambridge University Press, 2014)
The shift from government to governance has become a starting point for many studies of contemporary policy-making and democracy. Practices of Freedom takes a different approach, calling into question this dominant narrative and taking the variety, hybridity and dispersion of social and political practices as its focus of analysis. Bringing together leading scholars in democratic theory and critical policy studies, it draws upon new understandings of radical democracy, practice and interpretative analysis to emphasise the productive role of actors and political conflict in the formation and reproduction of contemporary forms of democratic governance. Integrating theoretical dialogues with detailed empirical studies, this book examines spaces for democratisation, institutional design, democratic criteria and learning, whilst mobilising the frameworks of agonistic and aversive democracy, informality and decentred legitimacy in cases from youth engagement to the Israeli-Palestinian conflict.
Machine generated contents note: 1. Introduction: democracy, conflict and participation in decentred governance Steven Griggs, Aletta J. Norval and Hendrik Wagenaar; 2. Governance-driven democratisation Mark E. Warren; 3. Beyond deliberation: agonistic and aversive grammars of democracy: the question of criteria Aletta J. Norval; 4. Designing democratic institutions for decentred governance: the Council of Europe's acquis Vivien Lowndes and Lawrence Pratchett; 5. Assessing the democratic anchorage of governance networks Eva Sørenson and Jacob Torfing; 6. Learning through contested governance: the practice of agonistic intersubjectivity John Forester; 7. Decentred legitimacy in the new community governance Steven Connelly; 8. Designing'the political' in (and out) of neighbourhood governance Helen Sullivan; 9. Participatory governance in practice Therese O'Toole and Richard Gale; 10. The agonistic experience: informality, hegemony, and the prospects for democratic governance Hendrik Wagenaar; 11. Insurgent citizenship: radicalism, co-optation, and neighbourhood geopolitics among the Palestinian citizens of Haifa, Israel Joseph Leibovitz.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Liberty; Democracy